Structural Stability of the Relationship between Indirect Taxes and Government Expenditure in Nepal: Implications for Fiscal Policy - Karki, Dipendra; Dahal, Rewan Kumar; Bhattarai, Ganesh; Gnawali, Laxman (Journal of Business and Social Sciences Research, 2023)
This study uses time series data of Nepal from fiscal years 1974/75 to 2017/18 to examine the dynamics of the relationship between indirect taxes and government spending. The study’s main objective is to examine the effect size of Value Added Tax (VAT), excise, and customs duties in predicting Nepal’s budget deficit. The data for the study purpose were obtained from the Government of Nepal, Ministry of Finance. The study used a retrospective methodology. The data were first checked for stationarity by employing the Augmented Dickey-Fuller Test, and then the link between the variables was determined using a multiple regression analysis based on ordinary least squares. The results showed that customs charges did not affect government spending in Nepal, while value-added and excise taxes had a statistically significant positive impact. The structural stability of the parameter was evaluated utilising the CUSUM and CUSUMSQ procedures. The results showed no evidence of misspecification or instability within the period predicted by the model. The residuals follow a normal distribution with no serial correlation, heteroscedasticity, or multicollinearity issues. The main implication of the study finding is that the government should exercise fiscal restraint and prioritise the collection of indirect taxes. Additionally, it recommends reducing customs taxes for new businesses and expanding the range of products subject to VAT.